Inequities in Children's Reading Skills: The Role of Home Reading and Preschool Attendance - Goldfeld, Sharon; Moreno-Betancur, Margarita; Guo, Shuaijun; Mensah, Fiona; O'Connor, Elodie; Gray, Sarah; Chong, Shiau; Woolfenden, Sue; Williams, Katrina; Kvalsvig, Amanda; Badland, Hannah; Azpitarte, Francisco; et al. (My University, 2021)
Children from socioeconomically disadvantaged backgrounds have poorer learning outcomes. These inequities are a significant public health issue, tracking forward to adverse health outcomes in adulthood. We examined the potential to reduce socioeconomic gaps in children's reading skills through increasing home reading and preschool attendance among disadvantaged children. We drew on data from the nationally representative birth cohort of the Longitudinal Study of Australian Children (N = 5107) to examine the impact of socioeconomic disadvantage (0-1 year) on children's reading skills (8-9 years). An interventional effects approach was applied to estimate the extent to which improving the levels of home reading (2-5 years) and preschool attendance (4-5 years) of socioeconomically disadvantaged children to be commensurate with their advantaged peers, could potentially reduce socioeconomic gaps in children's reading skills. Socioeconomically disadvantaged children had a higher risk of poor reading outcomes compared to more advantaged peers: absolute risk difference = 20.1% (95% confidence interval [CI]: 16.0%-24.2%). Results suggest that improving disadvantaged children's home reading and preschool attendance to the level of their advantaged peers could eliminate 6.5% and 2.1% of socioeconomic gaps in reading skills, respectively. However, large socioeconomic gaps would remain, with disadvantaged children maintaining an 18.3% (95% CI: 14.0%-22.7%) higher risk of poor reading outcomes in absolute terms. There are clear socioeconomic disparities in children's reading skills by late childhood. Findings suggest that interventions that improve home reading and preschool attendance may contribute to reducing these inequities, but alone are unlikely to be sufficient to close the equity gap.
Keywords: home reading; interventional effects; preschool attendance; reading skills; socioeconomic disadvantage; Disadvantage, adversity and resilience; Childhood and child development